Acquaintance with LGBTQI + People is Not Enough: Attitudes toward Same Sex Parents in Australia. Issue 5 (6th October 2022) - Sprajcer, Madeline; Bachmann, Alysa; Benveniste, Tessa; Lastella, Michele
Abstract: Although social acceptance of same sex parenting in Australia has improved, prejudice toward same sex parented families still exists. Using the contact hypothesis as a theoretical framework, the aim of this mixed methods study was to investigate the influence that personal contact with lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI+) people has on attitudes toward same sex parented families. A sample of Australian adults (n = 210) volunteered to participate in an online survey. Multiple regression analyses were used to investigate how number of LGBTQI + acquaintances, frequency of contact and closeness with LGBTQI + individuals impacted beliefs about same sex parenting and children's adjustment in same sex parented families. Results indicated that frequency and degree of contact with LGBTQI + individuals (but not number of acquaintances) were associated with positive attitudes toward same sex parenting. This novel finding indicates that close relationships (rather than simple acquaintance) with LGBTQI + individuals may be required to reduce prejudice toward same sex parented families.